Power generation by using piezoelectric transducer with bending mechanism support - Anis Maisarah Mohd Asry; Farahiyah Mustafa; Maizul Ishak; Aznizam Ahmad (Institute of Advanced Engineering and Science, 2019)
This paper presents about power generation by using piezoelectric transducer with bending mechanism support. In this study, bending mechanism is developed by employing 3D printer technology. This 3D model is used as a support for a piezoelectric transducer during deflection or bending process. During deflection condition, stress that applied on the piezoelectric transducer will generate electrical energy. The 3D model helps the piezoelectric transducer to produce more voltage output. A finger press test used as evaluation method for the voltage output of the piezoelectric transducer. The experiment is tested by varying three different 3D model with the different diameter for the middle hole for each of the model. A round shape of the piezoelectric transducer with size of 50 mm in diameter is used to conduct the experiment. Thus, when the piezoelectric transducer placed on the 3D model with 0 mm in diameter of middle hole will producing 5.4 V voltage output. However, 3D model with 30 mm diameter of middle hole, the output increases up to 19.0 V. The output voltage for piezoelectric transducer reached its highest voltage when placed on the 3D model with middle hole of 40 mm which is 34.4 V. This bending mechanism can be used to increase the output of piezoelectric transducer as it applied underneath footstep tile at crowded area to harvest the energy produced from walking activities. The power generated can be used to power up various electronic devices.